The SPARC DRC: Building a Resource for the Autonomic Nervous System Community - Osanlouy, Mahyar; Bandrowski, Anita; de Bono, Bernard; Brooks, David; Cassarà, Antonino M.; Christie, Richard; Ebrahimi, Nazanin; Gillespie, Tom; Grethe, Jeffrey S.; Guercio, Leonardo A.; Heal, Maci; Lin, Mabelle; et al. (Frontiers in Physiology, 2021)
The Data and Resource Center (DRC) of the NIH-funded SPARC program is developing databases, connectivity maps and simulation tools for the mammalian autonomic nervous system. The experimental data and mathematical models supplied to the DRC by the SPARC consortium are curated, annotated and semantically linked via a single knowIedgebase. A data portal has been developed that allows discovery of data and models both via semantic search and via an interface that includes Google Map-like 2D flatmaps for displaying connectivity, and 3D anatomical organ scaffolds that provide a common coordinate framework for cross-species comparisons. We discuss examples that illustrate the data pipeline, which includes data upload, curation, segmentation (for image data), registration against the flatmaps and scaffolds, and finally display via the web portal, including the link to freely available online computational facilities that will enable neuromodulation hypotheses to be investigated by the autonomic neuroscience community and device manufacturers.